Characteristics of Chilean children's advertising in times of greater access to the media and consumer goods - Uribe B., Rodrigo (Estudios de Administración, 2005)
The economic growth and the pervasiveness of the new information technologies have configured a new landscape in which children have gained an increasing access to consumption goods and commercial messages trying to reach their attention and interest. This piece of research represents a seminal study in the field of children advertising in Latin America. It examines the characteristics of advertisements aimed to children in a sample of Chilean TV from aerial and paid platforms. Results show that pieces of advertising aimed to children in this country tend to follow similar patterns as those detected in developed countries in terms of the level of presence of advertising, most advertised products and persuasive techniques used. However,important problems were detected in the use of those practices that facilitate children’s understanding of advertising.